2020
DOI: 10.1016/j.anr.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Death Education Intervention for Older People with Chronic Disease and Family Caregivers: A Quasi-Experimental Study

Abstract: Purpose: To investigate the effectiveness of a structured death education program for older adults with chronic illness and their family caregivers. Methods: This study adopted two-group, nonrandomized quasi-experimental design. Patientecaregiver dyads in the intervention group (N ¼ 40 dyads) engaged in the death education program at the bedside once a week for 5 weeks, and were compared with participants (N ¼ 40 dyads) in the control group who received usual health education. The program consisted of five ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(48 reference statements)
0
12
0
Order By: Relevance
“… Chen et al. ( Chen et al., 2020 ) Wuhan 2020 Asian Nursing Research (2019: 0.988) To investigate the effectiveness of a structured death education program 80 older adults with chronic illness and 80 related relatives Two-group, non-randomised quasi-experimental study consisting of 5 weeks bedside death education was delivered to the intervention group and 5 weeks usually health education to the placebo group (July-December 2019) Death education improved patients' death attitudes and satisfaction in relation to ‘usual practice’ (p=.002). Patients’ fear of death was significantly reduced by the death education program (p < .001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Chen et al. ( Chen et al., 2020 ) Wuhan 2020 Asian Nursing Research (2019: 0.988) To investigate the effectiveness of a structured death education program 80 older adults with chronic illness and 80 related relatives Two-group, non-randomised quasi-experimental study consisting of 5 weeks bedside death education was delivered to the intervention group and 5 weeks usually health education to the placebo group (July-December 2019) Death education improved patients' death attitudes and satisfaction in relation to ‘usual practice’ (p=.002). Patients’ fear of death was significantly reduced by the death education program (p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies explored the components of the ‘good death’ by focusing on end-of-life decision-making processes ( Gu et al., 2016 , Liu et al., 2016 ). Two studies had primarily educational aims ( Chen et al., 2020 , Cui et al., 2011 ), and one about pain management ( Deng et al., 2014 ). However, the ‘good death’ was touched in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, individuals should be educated about death and learn to acknowledge it as a natural part of life. Recent death education intervention studies conducted with the elderly (Chen et al, 2020), adolescents (Testoni, Ronconi, et al, 2019), and preschoolers and their parents (Testoni, Cordioli, et al, 2019) have found that death education has positive psychological and emotional outcomes. Scholars and professionals have long insisted on including death education in the K‐12 curriculum (Aspinall, 1996; Galende, 2015; Oaks & Bibeau, 1987; Smilie, 2021; Wass, 2004; Willis, 2002).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%